Central venous-to-arterial carbon dioxide difference in critically ill pediatric patients with septic shock - Chen, Rongxin (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2014)
OBJECTIVE: To assess the value of central venous-to-arterial carbon dioxide difference [ P( cv-a) CO₂] in evaluation of disease severity and prognosis in children with septic shock who already had central venous oxygen saturation (ScvO₂) higher than 70% after early resuscitation